Analysis on Expressive Illocutionary Act in The Maleficent 2 Movie - Maulana, Farhan (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
Film is a form of mass media that has audio and visual attributes, so that it can attract wider public interest. In this study, what the researcher wants to study and analyze is focused on illocutionary acts, especially in the film The Maleficent 2. The reason researchers want to study illocutionary acts is because they relate to problems that exist in society in everyday life, namely lack of communication or miss communication. This research applies a descriptive qualitative approach since it studied the kinds of expressive Illocutionary act used by the character of movie and know the function of expressive Illocutionary act in Maleficent 2 Movie using John R. Searle's theory. Based on the results of the study, the authors concluded that the data obtained in the Maleficent 2 film by Linda Woolverton, there are five types of illocutionary speech acts. The types of illocutionary speech acts uttered by the characters in the Maleficent 2 film are 18 assertive speech acts, 17 directive speech acts, 3 commissive speech acts, 14 expressive speech acts, and 9 declarative speech acts. The functions of expressive illocutionary acts used by the characters in Maleficent 2 film are 1 function of thanking, 3 functions of blaming, 1 function of accusing, 4 functions of praising, 3 functions of apologizing and 2 functions of congratulating.